2016
DOI: 10.2340/16501977-2053
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after stroke: The KOSCO Study

Abstract: Objective: To investigate the return to work status of patients with first-ever stroke with functional independence 6 months post-stroke. Design: Prospective cohort study. Participants: Nine hundred and thirty-three patients with functional independence at 6 months after stroke onset. Methods: A complete post-enumeration survey was performed through a review of the medical records for first admission. In addition, structured self-administered questionnaires and a face-to-face interview were performed assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 15 publications
(18 reference statements)
4
36
0
2
Order By: Relevance
“…The association between high scores and RTW could mean that people who RTW experience a higher health-related quality of life, but also that less problems in the domains that EQ-5D measure could facilitate RTW. Previous research supports a higher health-related quality of life in the RTW group [9, 41], which emphasizes the importance of optimizing the system of support people RTW.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The association between high scores and RTW could mean that people who RTW experience a higher health-related quality of life, but also that less problems in the domains that EQ-5D measure could facilitate RTW. Previous research supports a higher health-related quality of life in the RTW group [9, 41], which emphasizes the importance of optimizing the system of support people RTW.…”
Section: Discussionmentioning
confidence: 88%
“…A relatively modest number of possible predictors for RTW were used, resulting in the risk of important predictors and confounders being neglected. For instance, the type of occupation, educational level and comorbidity have shown to be significant factors in previous research [4143] but have not been considered here. Furthermore, the relatively large CI could indicate that there is relatively small number of participants in each subgroup, which results in an uncertainty regarding the exact OR/HR.…”
Section: Discussionmentioning
confidence: 99%
“…However, most cross-sectional or cohort studies did not confirm a relationship between the presence of spouses, family or friends and reengagement in valued activities. 33,34,38,39,45,46,6466 Sometimes, their presence was even found to worsen reengagement. 67 For a detailed description of the similarities and inconsistencies between findings and related levels of evidence, see Supplementary Table IV, last column; ‘synthesis’.…”
Section: Resultsmentioning
confidence: 99%
“…24,49,65,66,7586 Some single remaining studies on activities such as eating, exercise or leisure 30,31,8790 did not fit this format. In all the types of valued activities social support was identified as a facilitator to reengagement.…”
Section: Resultsmentioning
confidence: 99%
“…The KOSCO study from Korea reported that 60% returned to work at 6 months in a population of stroke victims with minor disabilities (Chang et al., 2016). Bonner et al.…”
Section: Discussionmentioning
confidence: 99%